2018
DOI: 10.1039/c7ce02013a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of “natural” diamonds by HPHT annealing of synthetic diamonds

Abstract: In this paper, IIa, Ib, N-doped and N–H co-doped diamonds were studied, and the interaction mechanisms between hydrogen and nitrogen in the diamonds were investigated in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…The single peak at ~750 cm −1 corresponds to Au-S bonds from gold nanoparticles. The additional peaks in the 1950-2,210 cm −1 range represent the artifacts of the diamond ATR setup (Fang et al, 2018). The FTIR results are in good agreement with previous reports (Thamri et al, 2016), confirming the presence of gold decorated -COOH functionalized MWCNTs in the coating.…”
Section: Fourier Transform Infra-red Spectroscopysupporting
confidence: 90%
“…The single peak at ~750 cm −1 corresponds to Au-S bonds from gold nanoparticles. The additional peaks in the 1950-2,210 cm −1 range represent the artifacts of the diamond ATR setup (Fang et al, 2018). The FTIR results are in good agreement with previous reports (Thamri et al, 2016), confirming the presence of gold decorated -COOH functionalized MWCNTs in the coating.…”
Section: Fourier Transform Infra-red Spectroscopysupporting
confidence: 90%
“…The appearance and relative intensity of these bands depends on the ND brand. These bands could be surface groups bound to metal species or nitrile [ 55 ] or other C–N–C, C–N–N and similar nitrogen-based vibrations [ 56 ], which may be the manifestation of N or N vacancy centers in the ND cores [ 57 ]. These bands were found in graphene [ 12 ] but require more studies in the case of nanodiamonds.…”
Section: Discussionmentioning
confidence: 99%
“…24 Pre-existing diamonds (natural or synthetic) can also be subject to further treatment by HPHT methods. One such recent study 25 has shown that appropriate annealing of HPHTgrown, N−H codoped SCDs with N content of ∼1000 ppm encourages aggregation of the nitrogen atoms (from C-centers to A-and B-centers). Such annealing reduces the visible coloration of these samples, especially in the {111} faces, thereby increasing their potential appeal and value.…”
Section: Laboratory-based Synthesis Of Diamond and Nitrogen-containin...mentioning
confidence: 99%